Online IRE Learning during the Covid-19 Pandemic in Yogyakarta Between Opportunities and Challenges - Awang Dhany Armansyah; Fitriah M. Suud (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
This article aims to determine the process and impact of online IRE (Islamic Religious Education) learning in Yogyakarta. This study uses a qualitative descriptive method with research subjects consisting of principals, teachers, students, and parents. The results of the study revealed that students can be categorized into three, namely those who like (1) face-to-face learning, (2) online learning, and (3) offline and online learning. However, among the three categories, the highest number is found in students who do not like online learning. A phenomenon was found that revealed that parents were bored with online learning and were unable to guide their children to study at home. The inhibiting factors for teachers include students being less active in learning, the difficulty of finding the right method so that students do not get bored quickly, and student assessments using family accounts. Parental barriers consist of parents who cannot teach their children during online learning, taking turns using mobile phones with their children, and parents who are busy working. While the supporting factors are learning quota assistance, the availability of computer laboratories, and parents always coordinating with teachers. Online learning has been shown to have an impact on students' economic, social and psychological conditions.